Karkheh Basin Focal Project - Ahmad, M.D.; Giordano, Mark (CGIAR Challenge Program on Water and Food, 2010)
The Karkheh Basin Focal Project was designed to collect and organize baseline information for future researchers and to highlight future research needs. All collected data is available in the IDIS system. The specific research findings and recommendations for the basin are 1) The use of non-agricultural water measures is likely to be a more effective solution to remaining rural poverty in the Karkheh basin and Iran; 2) In the short to medium term, agricultural water policy and research should focus on improvements in physical water productivity so as to improve the use scarce water resources for given national food security priorities and 3) in the longer term, shift towards economic water productivity by moving water away from lower productivity grain production and towards higher value agricultural and other activities including hydropower generation and urban uses.